Sweet lamb of heaven : [large type] a novel - Millet, Lydia, 1968- (Wheeler Publishing, 2016)
Blending domestic thriller and psychological horror, this compelling page-turner follows a mother fleeing her estranged husband. A double-edged and satisfying story with a strong female protagonist, a thrilling plot, and a creeping sense of the apocalyptic, Sweet Lamb of Heaven builds to a shattering ending with profound implications.